2004
DOI: 10.1128/iai.72.12.6817-6825.2004
|View full text |Cite
|
Sign up to set email alerts
|

NK Cells Contribute to the Control ofTrypanosoma cruziInfection by Killing Free Parasites by Perforin-Independent Mechanisms

Abstract: The protozoan parasite Trypanosoma cruzi circulates in the blood as trypomastigotes and invades a variety of cells to multiply intracellularly as amastigotes. The acute phase leads to an immune response that restricts the proliferation of the parasite. However, parasites are able to persist in different tissues, which causes the pathology of Chagas' disease. Natural killer (NK) cells play an important role in innate resistance to a variety of pathogens. In the present study we analyzed whether NK cells partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
55
1
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 34 publications
1
55
1
5
Order By: Relevance
“…This result should be interpreted with caution, however, because it would be impossible to attribute the high susceptibility of the IL-12/IL-23 (p40) KO mice only to a defect of specific CD8 ϩ T cells. The absence of this cytokine impairs a number of other immunological functions, including the expansion of Th1 CD4 ϩ T cells and NKT and NK cells, all of which actively participate during the immune response to T. cruzi infection (7,15,23,30,42).…”
Section: Discussionmentioning
confidence: 99%
“…This result should be interpreted with caution, however, because it would be impossible to attribute the high susceptibility of the IL-12/IL-23 (p40) KO mice only to a defect of specific CD8 ϩ T cells. The absence of this cytokine impairs a number of other immunological functions, including the expansion of Th1 CD4 ϩ T cells and NKT and NK cells, all of which actively participate during the immune response to T. cruzi infection (7,15,23,30,42).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental models have shown that NK cells play a crucial role in immunity against T. cruzi (27). However, the role of NK cells during human T. cruzi infection is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…However, these cells are thought to act early, secreting IFN-␥ (11,52). A role for cytolysis mediated by perforin has been discarded during NK direct contact-mediated lysis of T. cruzi or T. cruzi-infected cells (35,36). The role of NK cells in our system remains to be studied.…”
mentioning
confidence: 99%